The effect of acute cognitively engaging physical activity breaks on children's executive functions: Too much of a good thing?. (May 2018) - Egger, Fabienne; Conzelmann, Achim; Schmidt, Mirko
Abstract: Objectives: Acute bouts of physical activity may have an impact on children's executive functions. However, the role played by cognitive engagement (CE) during physical activity remains unclear. Therefore, the aim of the study was to disentangle the separate and/or combined effects of physical exertion (PE) and CE, induced by classroom-based physical activity, on children's executive functions. Design: In a 2 × 2 between-subjects experimental design, 216 children ( M age = 7.94, SD = 0.44, 49.1% girls) were randomly assigned to one of four conditions consisting of a classroom-based physical activity intervention varying in both physical exertion (high PE vs. low PE) and cognitive engagement (high CE vs. low CE). Methods: Executive functions (updating, inhibition, shifting) were measured before and immediately after a 20-min intervention. To test whether a potential change in children's executive functions was due to the main effect of PE or CE or an interaction of both, three separate ANCOVAs were conducted. Results: Contrary to the hypotheses, there was a significant, negative effect for the CE factor in shifting. No effects were found in either updating or inhibition. No significant effects were found for either the PE factor or the interaction of PE and CE in any of the executive functions. Conclusions: The results indicate that an acute bout of CE in classroom-based physical activity may deteriorate children's cognitive performance. These surprising results are discussed in the light of theories predicting both facilitating and deteriorating effects of cognitively engaging physical activity. Highlights: The role played by cognitive engagement during acute PA remains unclear. Four different types of classroom-based PA breaks were systematically compared. A negative effect for the factor cognitive engagement was found. The duration, depending on the specific PA type, should be adapted in terms of age.